The Effect of Problem-Based Learning Assisted by The PhET Simulation Application on Students' Learning Outcomes on The Temperature and Heat Material - Manalu, Nissi WF; Silaban, Bajongga; Nainggolan, Juliper (Jurnal Ilmu Pendidikan dan Sosial, 2025)
This study aims to determine the effect of the problem-based learning model assisted by the PhET Simulation application on student learning outcomes in the material of temperature and heat in class XI of GKPI Padang Bulan Medan Private High School. The research method used is a pre-experiment with a population of all class XI students of GKPI Padang Bulan Medan Private High School totaling 81 people. The sampling technique used is purposive sampling, and the sample is class XI IPA totaling 26 people. The instrument used is a multiple-choice learning outcome test consisting of 20 items. Before being given treatment to students, a prerequisite test was first carried out that the instrument used was indeed appropriate. Next, a pretest was given to students without any learning with an average score obtained of 24.42. After the pretest was given treatment, then continued with giving a posttest and the average score obtained was 83.65. To see the difference in pretest and posttest results, a one-tailed t-test was carried out with α = 0.05. From the results of data analysis with N-Gain, it was finally concluded that there was an influence of problem-based learning assisted by the PhET simulation application on the learning outcomes of class XI IPA students at GKPI Padang Bulan Medan Private High School on the material of temperature and heat